Pragmatic Analysis of Searle’s Directive Acts Types in “Get Out Movie” - Fanny Virginia; Zia Hisni Mubarak (English Department of Faculty of Tarbiyah and Teacher Training, 2022)
This descriptive qualitative research revealed directive acts types of characters’ directive utterances in a movie. The researchers took a thriller movie entitled Get Out as the data source and the characters' directive utterances were gathered as the data. Considering the data were collected through observation and note-taking, observational method and note-taking technique were applied. In analyzing data, the researchers employed pragmatic identity method and technique of pragmatic competence- in equalizing. The investigation was done by applying the theory parted by Searle (1979), which was further defined by Searle and Vanderveken (1985). The findings reported that there were 35 data of directive acts types and 10 directive acts types appeared in the utterances. Specifically, nine data were found in ask, command showed two data, order consisted of six data, one data in plead, beg, and entreat, permit got five data, request was discovered in two data, four data were found in advise, and invite consisted of four data. Among all types, the type of ask involved as the dominant type because the movie characters tended to convey directive utterances to direct other characters to answer questions. There was no type of pray conveyed in the characters' directive utterances as the characters did not privately speak to sacred figures or God.